SNP-based and pedigree-based estimation of heritability and maternal effect for body weight traits in an F2 intercross between Landrace and Jeju native black pigs - Hee-Bok Park; Sang-Hyun Han; Jae-Bong Lee; Sang-Geum Kim; Yong-Jun Kang; Hyun-Sook Shin; Sang-Min Shin; Ji-Hyang Kim; Jun-Kyu Son; Kwang-Soo Baek; Sang-Rae Cho; In-Cheol Cho (The Korean Society of Animal Reproduction and Biotechnology, 2016)
Growth traits, such as body weight, directly influence productivity and economic efficiency in the swine industry. In this study, we estimate heritability for body weight traits usinginformation from pedigree and genome-wide single nucleotide polymorphism (SNP) chip data. Four body weight phenotypes were measured in 1,105 F2 progeny from an intercross between Landrace and Jeju native black pigs. All experimental animals were subjected to genotypic analysis using PorcineSNP60K BeadChip platform, and 39,992 autosomal SNP markers filtered by quality control criteria were used to construct genomic relationship matrix for heritability estimation. Restricted maximum likelihood estimates of heritability were obtained using both genomic- and pedigree- relationship matrix in a linear mixed model. The heritability estimates using SNP information were smaller (0.36-0.55) than those which were estimated using pedigree information (0.62-0.97). To investigate effect of common environment, such as maternal effect, on heritability estimation, we included maternal effect as an additional random effect term in the linear mixed model analysis. We detected substantial proportions of phenotypic variance components were explained by maternal effect. And the heritability estimates using both pedigree and SNP information were decreased. Therefore, heritability estimates must be interpreted cautiously when there are obvious common environmental variance components.